Sutainabe Economic Development Ini Zakat: Islamic Perspektif - Tasdik Kulumudin; Wawan Abdul Rozak (Indonesian Research of Sustainability Management, Business, & Administration (IRHAMNA), 2025)
Background: Sustainable economic development requires an integrated approach that balances social equity, economic growth, and environmental sustainability (Rahmat & Apriliani, 2023). Zakat, as a fundamental pillar of Islam, serves as a redistributive financial mechanism that can contribute to poverty alleviation, income redistribution, and financial inclusion. However, its potential in achieving Sustainable Development Goals (SDGs) remains underexplored in mainstream economic literature. Methods: This study employs a qualitative research approach using content analysis of academic sources, policy documents, and institutional reports. A systematic literature review is conducted to examine zakat’s role in fostering sustainable economic development, particularly in relation to poverty reduction and social welfare enhancement. Thematic analysis is applied to identify recurring patterns and assess the institutional frameworks governing zakat collection and distribution. Results: The findings highlight that zakat, when effectively integrated into economic and social policies, serves as a powerful tool for income redistribution and financial empowerment. Productive zakat distribution towards micro, small, and medium enterprises (MSMEs) enhances financial stability. Digitalisation and regulatory reforms improve zakat governance, ensuring efficiency and transparency in its allocation. Conclusions: Zakat has the potential to align with SDGs, particularly in poverty eradication and economic justice. A maqāṣid al-sharīʿah-oriented framework in zakat management is essential for maximising its impact on sustainable development. Implications: Policymakers should integrate zakat with national development strategies and explore its synergy with waqf to establish long-term funding mechanisms for socio-economic projects. Limitations: The study focuses on zakat’s economic impact, with limited discussion on socio-cultural aspects. Governance variations across jurisdictions require further comparative studies.